The all-American golden boy: Robert Redford, blond hair and masculinity in Hollywood. Issue 1 (2nd January 2016) - Wright, Julie Lobalzo
Abstract : Although there are, evidently, male stars with blond hair in Hollywood, male blondness seems to pose a problem. Unlike their female equivalents, few male stars, if any, have been defined by their blondness, mainly due to the feminine connotations implicit in the term. However, instead of being burdened by this association, Robert Redford stands as one of the few male Hollywood stars who utilised his blondness to promote an all-American golden boy image that was both romantic and political. Drawing on films from the height of his stardom, approximately 1972–1985, this essay seeks to demonstrate how Redford's films exploited his blond image, often comparing his extreme whiteness with dark-haired partners, to project an idealised, sometimes even superhuman, image of American masculinity.